A stable metal–organic framework with suitable pore sizes and rich uncoordinated nitrogen atoms on the internal surface of micropores for highly efficient CO2 capture1. Issue 14 (14th April 2015) - Bao, Shao-Juan; Krishna, Rajamani; He, Ya-Bing; Qin, Jun-Sheng; Su, Zhong-Min; Li, Shun-Li; Xie, Wei; Du, Dong-Ying; He, Wen-Wen; Zhang, Shu-Ran; Lan, Ya-Qian
<x xml:space="preserve">Abstract</x> A highly stable tetrazolate-containing framework (NENU-520) has been successfully synthesized. NENU-520 exhibits exceptionally high selectivity for CO2/N2 at 298 K.